CANCEL CULTURE DICTIONARY : AN A TO Z GUIDE TO WINNING THE WAR ON FUN - Failla, Jimmy (New York, NY : Fox News Books, 2024)
"A series of articles, listed alphabetically, about cancel culture" --
Keywords: Cancel culture; Public opinion; Social distance; Social influence